Respon imun benih ikan mas, Cyprinus carpio, yang diberi pakan probiotik Lactobacillus sp. dengan konsentrasi berbeda - Pangalila, Novelia; Manoppo, Henky; Tumbol, Reiny A.; Lumenta, Cyska; Kreckhoff, Reni L.; Warouw, Veibe (Universitas Sam Ratulangi, 2020)
The research aimed to isolate probiotic bacteria from catfish intestine and assign the concentration of probiotic bacteria which effectively increase the activity of phagocytosis and total leukocytes of carp fingerlings. The fish was taken from Balai Pengembangan dan Pembinaan Pembudidayaan Ikan (BP3I) Tateli. Fish (average initial weight of 2.27 g) were acclimated for one week in 15 aquaria with a density of 25 fish/aquarium. One week after acclimatization, fish were fed with food added with probiotics with different concentrations, namely 1x106, 1x107, 1x108, 1x109 cfu/mL for four weeks. The dose of feed was 5% /body weight/day and feeding time was at 08.00 and 17.00. Data collected were phagocytosis and total leukocyte count. The results showed that supplementation of probiotic significantly increased phagocytic activity and total leukocytes (p<0.01). The best phagocytic activity and total leukocytes were achived in fish fed diet added with probiotics 1x108 cfu/mL. It can be concluded that supplementation of Â probiotic onto feed can increase phagocytic activity and total leukocytes of carp.